Durable efficacy of anlotinib in a patient with advanced thymic squamous cell carcinoma after multiline chemotherapy and apatinib: A case report and literature review. Issue 11 (30th September 2020) - Zuo, Ran; Zhang, Cuicui; Lin, Li; Meng, Zhaoting; Wang, Yajie; Su, Yudong; Abudurazik, Mihray; Du, Ye; Chen, Peng
Abstract : Thymic carcinoma is a rare and highly aggressive mediastinal tumor. Most patients are diagnosed at surgically unresectable stages. Current prospective and retrospective studies have indicated that platinum and anthracycline‐based chemotherapy are the first choice drugs of first‐line therapy for advanced thymic carcinoma. However, there is no optimal treatment after progression for patients who have undergone first‐line and subsequent chemotherapy. Anlotinib, a novel small molecule tyrosine kinase multitarget inhibitor, was approved by the China Food and Drug Administration as a third‐line treatment for advanced non‐small cell lung cancer (NSCLC) in May 2018. Herein we report a case of an advanced thymic squamous cell carcinoma patient harboring EGFR exon 20 insertion who had previously received multiline therapy, including chemotherapy, radiotherapy as well as antiangiogenic therapy. Also as an angiogenesis inhibitor, anotinib had controlled his mediastinal mass after failure of the apatinib treatment. To date, over 23 months of progression‐free survival (PFS) and six years of overall survival (OS) have been achieved. Compared with apatinib, the adverse reactions have been mild and tolerable and the patient's quality of life has improved. To our knowledge, this is the first report where anlotinib has been effective in controlling the progression of thymic carcinoma. In the multiline treatment of advanced thymic carcinoma, anlotinib appears to show great potential when utilized as a salvage treatment. Abstract : We present the case of a patient with an advanced TC harboring EGFR exon 20 insertion who successively benefited from two antiangiogenic agents after multiline therapy. After the failure of one tyrosine kinase inhibitor, the other was still active and effectively controlled the growth of the lesion.